The Effect of Combination Bay Leaf Stew and Ginger on Uric Acid Level - Aqila Saputri; Achmad Fauzi (STIKep PPNI Jawa Barat, 2023)
Aims: According to the WHO, there were 230 million gout sufferers in 2007, and that number is expected to rise dramatically by 2020. The average age of gout patients is 40-59 years old, and the number of sufferers has increased since 2000. Few people with gout are well-managed, and gout prevalence is increasing in both developed and developing countries (Yankusuma and Putri, 2016). During September and October 2022, data obtained from 30 senior citizens in Wanasari Village, Kp.Utan, Cibitung District, Bekasi Regency revealed that 12 of the elderly had increased uric acid levels. In September 2022, 12 senior individuals with increased uric acid levels were discovered in Wanasari Village, Kp.Utan, Cibitung District, Bekasi Regency. Using the data shown above, it is clear that there are still many elderly persons who have high uric acid levels. Method: This study design employs an experimental (pre-experimental) approach, using a one-group pretest posttest design, that is, a design that does not employ a control group, but instead performs the first observation (pretest), allowing testing of changes that occur after the experiment. Result: In September 2022, the average uric acid level of the elderly in Wanasari Village Kp.Utan, Cibitung District, Bekasi Regency was 8.94 before they were administered a combination of boiled bay leaves and ginger. In September 2022, the average uric acid level among the elderly in Wanasari Village Kp.Utan, Cibitung District, Bekasi Regency was 5.55 after they were administered a decoction of bay leaves and ginger. Conclusion: The combination of steamed bay leaves and ginger has a significant effect on reducing uric acid levels in the elderly in Wanasari Village, Kp.Utan, Cibitung District, Bekasi Regency in September 2022 (p value = 0.000).